Therapeutic effects of Ligularia stenocephala against inflammatory bowel disease by regulating antioxidant and inflammatory mediators. Issue 6 (2nd November 2017) - Debnath, Trishna; Kim, Eun-Kyung; Deb Nath, Narayan Chandra; Lee, Kwang-Geun
ABSTRACT: In this report, we studied the effect of leaf extracts of Ligularia stenocephala (LS) on inflammatory bowel disease (IBD) by regulating antioxidant and inflammatory mediators. The water extracts (LSW) exhibited more antioxidant activity than that of ethanol extracts (LSE). The extracts suppress the formation of nitric oxide by down-regulating the inducible nitric oxide synthase and pro-inflammatory cytokines (eg tumor necrosis factor alpha, interleukin (IL)-6, IL-10 and IL-1β expression) through the suppression of nuclear factor-ĸβ activation and mitogen-activated protein kinases phosphorylation in lipopolysaccharide-stimulated macrophage cells. Our in vivo study reveals that the extracts could suppress tissue damage significantly in mice colon. The expression regarding immune-related cytokines was also down-regulated by the extracts of LS leaf. Thus, it is concluded that the extracts could be used as a functional food, which could reduce the formation of oxidants, inflammation and IBD effectively. GRAPHICAL ABSTRACT: